(untitled) (Journal of Applied Oral Science, 2009)
OBJECTIVE: Follicular dendritic cells (FDCs) and interdigitating dendritic cells (IDCs) are dendritic cells found in lymphoid follicles, reactive follicles and in lymphomas. The goal of this study was to evaluate the presence and distribution of FDCs and IDCs in oral lymphomas. MATERIAL AND METHODS: Immunohistochemistry reactions were applied to 50 oral lymphomas using the antibodies anti-CD21, anti-CD35 and anti-caldesmon to FDCs, and anti-S100 protein to IDCs. Caldesmon+/FDCs and S100+/IDCs were quantified in Imagelab® software. RESULTS: FDCs revealed by CD21 and CD35 were positively stained in two cases of diffuse large B-cell lymphoma, one MALT lymphoma, and in one case of mantle cell lymphoma. FDCs were immunopositive to caldesmon in all cases, as well as IDCs to S100 protein. Burkitt lymphoma presented a lower amount of caldesmon+/FDCs and S100+/IDCs than diffuse large B-cell lymphoma and plasmablastic lymphoma of the oral mucosa type. CONCLUSIONS: The microenvironment determined by neoplastic lymphoid cells in oral lymphomas is responsible by the development and expression of dendritic cells types.